Williams’ False Dilemma: How to Give Categorically Binding Impartial Reasons to Real Agents - Beyleveld, Deryck (Journal of moral philosophy, 2013)
According to Bernard Williams, attempts to justify a categorically binding impartial principle fail because they can only establish categorically binding requirements on action by making them non-universalizable (Gewirth), and can only establish impartial requirements by rendering them inapplicable to real agents (Kant). But, an individual cannot be the particular agent the individual is without being an agent every bit as much as an individual cannot be an agent without being the particular agent that the individual is. On this basis, it is argued that, when the actual Gewirthian argument for a categorically binding impartial principle is presented, which Williams does not do, his objections to it do not hold and the argument establishes that agents are categorically bound to accept a substantive impartial principle that, at the same time, permits them to live lives that respect their own personal interests. Consequently, Williams’ dilemma is false.